Minat Berprofesi Di Bidang Perpajakan Sebelum Dan Sesudah Mengikuti Brevet Pajak - Omi Pramiana; Firdhatul Umroh; Alfiary Pradana Mellenio; Arina Mustofia (CV ODIS, 2021)
Career options are certainly something that should be considered by most students, especially career interests in taxation. A career in taxation is certainly not a profession that is mostly in the interest of students but to learn more about taxation, students will increase their knowledge by doing tax brevet. This research was conducted to find out if there are differences in career interest in the field of student taxation STIE PGRI Dewantara before and after doing tax brevet. Career interest in taxation is a desire of students in determining a career, especially in the field of taxation not only to be a tax consultant but also in the field of tax finance, while to support a career in the field of taxation it is necessary to add insight through the tax brevet where the tax brevet in STIE PGRI Dewantara consists of brevet A /B. This study uses a sample of 167 students of STIE PGRI Dewantara who have followed the tax brevet. Data collection method using questionnaires, data analysis using different test paired sample t-test. The results showed that there was a significant difference in the interest of career students in the field of taxation before and after attending the tax brevet.